2005
DOI: 10.1038/sj.ijo.0802929
|View full text |Cite
|
Sign up to set email alerts
|

Lower-body fat mass as an independent marker of insulin sensitivity—the role of adiponectin

Abstract: AIMS:To study the association between lower-body fat and estimates of whole-body insulin sensitivity in middle-aged men with and without a history of juvenile onset obesity, and to determine the possible mediating role of fasting serum adiponectin level as an insulin-sensitizing peptide. METHODS: A total of 401 men aged 39-65 y, body mass index 18-54 kg/m 2 , participated in the study. The following variables were measured on the study participants: regional body fat distribution as assessed by dual energy X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 39 publications
4
49
0
3
Order By: Relevance
“…92 Moreover, higher gluteofemoral fat mass results in higher adiponectin levels and increased insulin sensitivity. 16,93 There is a negative association between adiponectin and waist-to-hip ratio, central fat mass accumulation and visceral fat mass. 6,88,[94][95][96][97] Further, in vitro studies have shown that adiponectin protein content and mRNA expression are lower in visceral adipocytes 98 and that with increasing visceral fat mass adiponectin secretion from those cells is decreased, whereas secretion rates from subcutaneous adipocytes remain unaffected.…”
Section: Adiponectinmentioning
confidence: 99%
“…92 Moreover, higher gluteofemoral fat mass results in higher adiponectin levels and increased insulin sensitivity. 16,93 There is a negative association between adiponectin and waist-to-hip ratio, central fat mass accumulation and visceral fat mass. 6,88,[94][95][96][97] Further, in vitro studies have shown that adiponectin protein content and mRNA expression are lower in visceral adipocytes 98 and that with increasing visceral fat mass adiponectin secretion from those cells is decreased, whereas secretion rates from subcutaneous adipocytes remain unaffected.…”
Section: Adiponectinmentioning
confidence: 99%
“…Une accumulation de graisse périphérique, caractérisée par un rapport tour de taille/tour de hanches abaissé, est associée à un taux plasmatique élevé d'adiponectine, à une bonne sensibilité à l'insuline et à un profil lipidique plus favorable (taux de cholestérol total et de triglycérides plus bas et taux de cholestérol HDL plus élevé) [46]. La graisse glutéofémorale aurait donc un rôle cardioprotecteur [27].…”
Section: Rôle Protecteur De La Graisse Glutéofémoraleunclassified
“…Cette hormone adipocytaire augmente la sensibilité à l'insuline du foie et des muscles striés squelettiques [48]. Les sujets obèses sensibles à l'insuline ont des taux d'adiponectine significa-tivement plus élevés que les sujets obèses résistants à l'insuline, indépendamment de l'IMC et du tour de taille [46,49]. Les taux d'adiponectine sont plus élevés chez les MHO caractérisés par une meilleure sensibilité à l'insuline [12,46].…”
Section: Rôle Protecteur De La Graisse Glutéofémoraleunclassified
See 1 more Smart Citation
“…Lower circulating adiponectin levels compared to normal controls have been observed in human subjects with obesity, type 2 diabetes mellitus and/ or cardiovascular diseases in some reports [2][3][4]. In the absence of pharmacological agents, increases in circulating adiponectin levels are associated with a decrease in body weight [5,6], a reduction in lower body fat [7] and improved insulin sensitivity [8].…”
Section: Introductionmentioning
confidence: 99%